Evladı Fatihan in Macedonia (Problems-Suggestions of Solution) - Eyüp Kul (Avrasya İncelemeleri Dergisi)
Macedonia, which was founded in 1991 after the dissolution of the Republic of Yugoslavia, is one of the small countries of the Balkans. Macedonia has faced different problems since the year it was founded due to the influence of the different ethnic and religious populations it hosts, and has continued its existence with the agreements it signed with the intervention of the great powers. Especially in the country where a new constitutional order was established with the Ohrid Framework Agreement, the population other than the Macedonians had many rights. In this study, the problems faced by the Turks, who are one of the original elements of the country and whose population has decreased significantly with migrations and who have been called Evlad-ı Fatihan in these lands for centuries, after the establishment of the Macedonian State, are evaluated, and the policies and solutions that can be developed in response to these problems are examined.